Meditations About the Implications of the Seventh Wittgensteinian Aphorism in the Associative Speech of the Psychoanalytical Subject: whereof one cannot speak thereof one must (Really) be silent? - Boettcher Brandes, Adriano (2020)
This essay aims to reflect, specifically, about the statement “Whereof one cannot speak, thereof one must be silent”, seventh aphorism of Ludwig Wittgenstein’s Tractatus Logico-Philosophicus, and its implications on the symbolic capacity of the speaking subject who is concerned in psychoanalytic theory. The fact of having psychism, fruit of a structured language, is the item that makes the human being unique in nature and differentiates us from other animals. What is the price we pay for not speaking about some things?